2020
DOI: 10.1038/s41467-020-17720-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis links diverse hypothalamic cell types to fibroblast growth factor 1-induced sustained diabetes remission

Abstract: In rodent models of type 2 diabetes (T2D), sustained remission of hyperglycemia can be induced by a single intracerebroventricular (icv) injection of fibroblast growth factor 1 (FGF1), and the mediobasal hypothalamus (MBH) was recently implicated as the brain area responsible for this effect. To better understand the cellular response to FGF1 in the MBH, we sequenced >79,000 single-cell transcriptomes from the hypothalamus of diabetic Lepob/ob mice obtained on Days 1 and 5 after icv injection of either FGF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 66 publications
(136 reference statements)
3
50
0
Order By: Relevance
“…While mechanisms underlying the sustained glucoselowering action of FGF1 in the MBH await additional study, our recent work points to a role for glia-neuron interactions [55] and associations with FGF1-induced changes in the extracellular matrix [56]. Whatever the mechanism, the data collectively suggest that in rodent models of type 2 diabetes, hyperglycaemia arises from pathological processes that can be corrected (or overridden) through the hypothalamic action of FGF1.…”
Section: Targeting the Brain To Restore Normoglycaemia In Rodent Modementioning
confidence: 78%
“…While mechanisms underlying the sustained glucoselowering action of FGF1 in the MBH await additional study, our recent work points to a role for glia-neuron interactions [55] and associations with FGF1-induced changes in the extracellular matrix [56]. Whatever the mechanism, the data collectively suggest that in rodent models of type 2 diabetes, hyperglycaemia arises from pathological processes that can be corrected (or overridden) through the hypothalamic action of FGF1.…”
Section: Targeting the Brain To Restore Normoglycaemia In Rodent Modementioning
confidence: 78%
“…Based on previous work showing that tanycytes and astrocytes are especially responsive to the effect of icv FGF1 injection to induce sustained ERK1/2 signaling 5,7 , we next examined the response of these cell types following icv injection of FGF1 R50E. As anticipated, we observed that compared to icv injection of native FGF1, pERK1/2 induction in both tanycytes (Figure 3B) and astrocytes (Figure 3C) was markedly reduced at the 14h time point after icv injection of FGF1 R50E.…”
Section: Resultsmentioning
confidence: 99%
“…The interpretation of findings reported herein is also informed by recent work that has shed light on how the hypothalamus responds to FGF1. For example, intact hypothalamic melanocortin signaling (determined by interactions between Agrp and Pomc neurons in the ARC) appears to be required for sustained glucose lowering induced by icv FGF1 injection, but is dispensable for acute, transient effects of FGF1 on food intake, body weight, and glycemia 7 . In light of our current findings, this work suggests that diabetes remission induced by icv FGF1 involves a MAPK/ERK-dependent mechanism for enhanced melanocortin signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations